Ecole des Annals and Iraqi Perception: Its Impact on Early Iraqi Historians - Hassan, Nagham Abd AL-Hadi Mahdi; Al-Qaysi, Mahmoud Abdulwahid M. (Al-Adab Journal, 2021)
The article is a study of the Ecole des annals’ impact on the first generation of Iraqi historians and historiography during the 20th century. The Ecole des annals had emerged as a reaction of the 1st world war disasters and its destructive results which implicated on the political, economic and intellectual situations in Europe during the interwar period. The school had founded in 1929 by two French historians: Marc Bloch (1886-1944) and Lucien Febvre (1878-1956), and published its first journal " Annales d’histoire économique et sociale", in addition to publications of the school which concentrated on social and economic history, and kept away from the political history which was the main interest of "École méthodique" (Methodological school) since late 19th century and its journal " Revue historique" at 1876. The annals school had important influences on the European and American, and then world historiography since its rise up to present. The school had moved the historiography from political and diplomatic aspects to social, intellectual and economic issues.